Proxemics study on the school activity performance of filipino students establishing a guideline for sociopetal and sociofugal spaces in the library design of universities in Davao City - Tantano, Krisna Liz B.; Sebastian, Myrafe L. (2016)
Personal space has been one of the major bases for human interactions. A person?s way of distancing himself from others depending on any given situation shows how they react and make themselves comfortable during different set-ups. Proxemics is the wherein these interpersonal distances are explored. In this study, proxemics is studied for its role on the sociopetal ( a space that encourages interaction). And sociofugal ( a spaces that discourages interaction). University libraries serve as a space wherein the type of sociopetal and sociofugal interactions can be observed. Several study area set-ups show the need of the users for their different purposes of using the library. To establish a sociofugal and sociopetal space with proxemics consideration can promote a more functional and positive effects for the users. The libraries of Davao City were the scope of this study. Students were observed on their behavior in their respective libraries as well as noting on the different architectural elements of the libraries supported by a photo documentation. Students from these libraries were also ask to answer survey forms that focuses on questions regarding how their library space affects their privacy, comfort and efficiency during their individual and group activities. A one-day workshop was also conducted with willing college-level participants. The workshop was composed of three activities that included a simulation for the participants in situations where they were to place in a grouped wherein they have close relationships, another where they were placed in a group wherein they have distant relationships, and lastly, an activity for an individual setting. The different guidelines in library space configurations and layouts were obtained by combining the observations and the photos collected while visiting the five libraries and then comparing these to the survey results. The particular guidelines for the sociopetal and sociofugal spaces were acquired from the activity sheets gathered from the survey. Mean distance were calculated from the models made by the participants during the different activities in the workshop. The results made up for the different guidelines in planning a university library. In particular, the design consifderations for the sociopetal and sociofugal space especially concerning the layout, orientations, distances, and types of furniture to use.
Thesis (BS Architecture) -- University of the Philippines Mindanao, June 2016.